Analysis of History Textbooks based on Benedict Anderson's Approach - Syahputra, M. Afrillyan Dwi; Mahdiana, Nabillah (HISTORIKA, 2019)
This study aims to analyze the planting of nationalism, which is done through history textbooks. The problems discussed are: (1) In this study, how does the history textbook of class XI explain nationalism in line with Benedict Anderson's theory? (2) How can Print Capitalism Products in a textbook cause nationalism? This study used history textbooks for semester 2 grade XI. The method applied is a content analysis that includes an integrated view of the conversation/text and its specific context. Content Analysis is more than just counting words or extracting actual content from text to examine meanings, themes, and patterns that may be real or latent in a particular text. The approach used is nationalism, according to Benedict Anderson, which is a product of capitalism. The results show that textbooks can connect one person to another because they read the same writing so that the same nationalism arises. Print capitalism, like newspapers, can shape collective awareness and for its readers. From a variety of information in print, this is gradually raising awareness of the importance of equality, so building Language Connection (Language Relations). Benedict Anderson said that Benedict Anderson nationalism is a nation with values because there are individuals who consider themselves a community.